The role of virus infections in Sjögren’s syndrome - Maslinska, Maria; Kostyra-Grabczak, Kinga (Frontiers in Immunology, 2022)
Primary Sjögren’s syndrome (pSS) is an autoimmune disease with a clinical picture of not only mainly exocrine gland involvement, with dryness symptoms, but also internal organ and systems involvement. The epithelial damage and releasing of antigens, which, in some circumstances, become autoantigens, underlay the pathogenesis of pSS. The activation of autoimmune processes in pSS leads to the hyperactivation of B cells with autoantibody production and other immunological phenomena such as hypergammaglobulinemia, production of cryoglobulins, or formation of extra-nodal lymphoid tissue. Among the risk factors for the development of this disease are viral infections, which themselves can activate autoimmune reactions and influence the host’s immune response. It is known that viruses, through various mechanisms, can influence the immune system and initiate autoimmune reactions. These mechanisms include molecular mimicry, bystander activation, production of superantigens—proteins encoded by viruses—or a programming to produce viral cytokines similar to host cytokines such as, e.g., interleukin-10. Of particular importance for pSS are viruses which not only, as expected, activate the interferon pathway but also play a particular role, directly or indirectly, in B cell activation or present tropism to organs also targeted in the course of pSS. This article is an attempt to present the current knowledge of the influence specific viruses have on the development and course of pSS.